PENDIDIKAN MULTIKULTURAL: SINERGI ANTARA BAHASA INGGRIS DAN KEARIFAN LOKAL NIAS - Telaumbanu, Tatema (LPPM Universitas Nias Raya, 2024)
Multicultural education is an important approach to creating an inclusive learning environment that values cultural diversity. This study explores the synergy between English language teaching and the local wisdom of Nias, an area with unique cultural richness. Through literature analysis, this research demonstrates that integrating local wisdom into English language teaching can enhance students' communication skills and strengthen their cultural identity. This approach not only enriches the learning experience but also encourages students to appreciate local values while developing relevant English language skills in a global context. The study recommends the development of a curriculum that incorporates elements of local wisdom and training for teachers to support more effective implementation of multicultural education.